2008
DOI: 10.1007/s12088-008-0053-y
|View full text |Cite
|
Sign up to set email alerts
|

Studies on leaf spot disease of Withania somnifera and its impact on secondary metabolites

Abstract: During an investigation of the disease profi le of Withania somnifera, it was observed that leaf spot is the most prevalent disease. Repeated isolations from infected leaf tissues and pathogenicity tests showed the association of fungal pathogen identifi ed as Alternaria alternata (Fr.) Keissler. Scanning electron microscopy showed various histological changes in the leaf tissues of infected plants. A decrease in total content of reducing sugars (20%) and chlorophyll (26.5%) was observed in diseased leaves whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 19 publications
0
31
1
1
Order By: Relevance
“…It has been used in traditional medicine for the treatment of Alzheimer's disease, arthritis, cardiovascular disease, cold, dementia, dropsy, fever, female disorders, and hiccups (Kirtikar and Basu, 1975). Phytochemical studies revealed that W. somnifera contains a number of active constituents such as alkaloids, flavonoids and steroidal lactones (Pati et al, 2008;Mirjalili et al, 2009). In recent years, the demand for this plant species has sharply risen due to its biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used in traditional medicine for the treatment of Alzheimer's disease, arthritis, cardiovascular disease, cold, dementia, dropsy, fever, female disorders, and hiccups (Kirtikar and Basu, 1975). Phytochemical studies revealed that W. somnifera contains a number of active constituents such as alkaloids, flavonoids and steroidal lactones (Pati et al, 2008;Mirjalili et al, 2009). In recent years, the demand for this plant species has sharply risen due to its biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…5c) [27] which was changed into a dense surface morphology after hybridization with ssG-DNA of N. meningitidis from patient CSF (Fig. 5d) [28].…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…But the crop is mainly attacked by fungal pathogens under field conditions, although deterioration of these crops due to other diseases has also been reported. Leaf spot is the most prevalent disease of W. somnifera Alternaria alternata caused by a fungus (Pati et al, 2008). The plant has also been reported to be affected by many other foliar diseases.…”
Section: Several Diseases Affectmentioning
confidence: 99%